LEGAL POSITIVISM: A COMPARATIVE STUDY OF MODERNITY IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Sulaiman; Syaifuddin; Syamsuddin; Hajairin (Awang Long Law Review, 2025)
In practice and reality, legal positivism tends to be detrimental to justice seekers, legal positivism is formal and can only realize justice procedurally. This study uses normative legal research to inventory positive law, find legal principles and doctrines, with several approaches, the first is the Legislative Approach, Second, the conceptual approach is carried out by examining concepts, theories and opinions of experts that are related to the object being studied. Third, the comparative approach is a way of comparing to understand the law. The results of the study show that the law itself is always viewed as written law (law as it written in the books) in the text of legislation or law is law (law is law) only, even though the law itself should also be seen from the facts that occur in the field, for example those processed in court hearings. However, in positive law, the police, prosecutors and judges or other formal legal institutions cannot be blamed because they only fulfill and implement the formulation of the law which does not provide an opportunity for law enforcement officers to act according to their conscience. Even though judges are given freedom according to their conscience, if faced with complete evidence, there is no reason for the judge not to decide the case. Therefore, in the author's opinion, legal positivism is seen as unable to realize substantively just law for justice seekers but is only able to realize formal legal certainty and procedural justice in the implementation of the criminal justice system.